Early crack resistance of wood fiber-modified concrete containing nano-CaCO3 - Fan Lin; Zhihong Ran; Guanyu Cao; Xingrui Li (Case Studies in Construction Materials, 2025)
Although the addition of nano-CaCO3 (NC) can improve the mechanical properties of concrete, it exhibits a propensity for agglomeration, which affects the performance of the concrete. Additionally, it accelerates the hydration reaction of concrete, resulting in increased early hydration heat and susceptibility to early cracking. As a type of fiber reinforced concrete (FRC), wood fiber affects the mechanical properties of concrete and, like superabsorbent polymers (SAP), has water absorption properties that can be used as an internal curing material to improve the crack resistance of concrete. Therefore, this study investigated the feasibility of using low-cost wood fiber to modify concrete containing NC to enhance its early crack resistance. The wood fibers concentration comprising 0.24 % of the cement mass was selected for this study. The experimental results indicate that the incorporation of wood fibers in concrete containing NC reduces the mechanical properties slightly. However, by reducing the water and cement content by 10 %, NC agglomeration can be effectively prevented, leading to a denser internal structure and enhanced mechanical properties. Furthermore, the incorporation of wood fiber reduced the total early peak hydration heat of concrete containing NC by 5 %. In early crack resistance tests, the average crack area increased from 7.8 mm² to 52.2 mm², and the crack area per unit area increased from 206 mm²/m² to 1671 mm²/m², when compared to the reference concrete. After modification with wood fiber, these values were reduced to 40.9 mm² and 1023 mm²/m², respectively.